Selective increase of the permeability of polarized epithelial cell monolayers by Helicobacter pylori vacuolating toxin. - Papini, E (1998)
The effects of the vacuolating toxin (VacA) released by pathogenic strains of Helicobacter pylori on several polarized epithelial monolayers were investigated. Trans-epithelial electric resistance (TER) of monolayers formed by canine kidney MDCK I, human gut T84, and murine mammary gland epH4, was lowered by acid-activated VacA. Independent of the cell type and of the starting TER value, VacA reduced it to a minimal value of 1,000-1,300 Omega x cm2. TER decrease was paralleled by a three- to fourfold increase of [14C]-mannitol (molecular weight 182.2) and a twofold increase of [14C]-sucrose (molecular weight 342.3) transmonolayer flux. On the contrary, transmembrane flux of the proinflammatory model tripeptide [14C]-N-formyl-Met-Leu-Phe (molecular weight 437.6), of [3H]-inuline (molecular weight 5,000) and of HRP (molecular weight 47,000) did not change. These data indicate that VacA increases paracellular epithelial permeability to molecules with molecular weight < 350-440. Accordingly, the epithelial permeability of Fe3+ and Ni2+ ions, essential for H. pylori survival in vivo, was also increased by VacA. High-resolution immunofluorescence and SDS-PAGE analysis failed to reveal alterations of junctional proteins ZO-1, occludin, cingulin, and E-cadherin. It is proposed that induction by VacA of a selective permeabilization of the epithelial paracellular route to low molecular weight molecules and ions may serve to supply nutrients, which favor H. pylori growth in vivo.